KEMAMPUAN KOMITMEN ORGANISASI DALAM MEMODERASI PENGARUH PROFESIONALISME DAN INDEPENDENSI PADA KINERJA AUDITOR - Arya Aditya, Gede Ngurah Indra; Dwirandra, A.A.N.B.; Asmara Putra, I Nyoman Wijana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.09.TAHUN 2016, 2016)
The purpose of this study to obtain empirical evidence of the influence of the professionalism and independence of the auditor's performance, as well as the influence of organizational commitment moderating influence on the professionalism and independence of the auditor performance. This study used a questionnaire as a primary data. Auditors who worked in public accounting in Bali as many as 64 respondents auditors is obtained using purposive sampling technique. Data analysis technique used is multiple regression analysis and moderation regression analysis to see the coefficient of determination, the value of F statistics and statistical values ??t.The results obtained are professionalism effect on the performance of auditors, auditor independence affects the performance, organizational commitment strengthen the influence of professionalism in the performance of auditors, and organizational commitment to strengthen the influence on the performance of auditor independence. Organizational commitment can be categorized as quasi moderation in this study.
Keywords: Performanceof Auditor, Professionalism, Independence, Organizational Commitment